Forward Modeling and Seismic Wave Inversion for Amplification Analysis in The Java Subduction Zone Using Python - Yudha, Pradipta Kusuma; Yulianto, Agus (Universitas Padjadjaran, 2026)
This study aims to analyze seismic wave propagation and amplification in the Java subduction zone using a numerical modeling approach. The method integrates forward modeling and seismic inversion within a two-dimensional finite difference framework to simulate wave behavior in heterogeneous subsurface conditions. Secondary data, including seismic velocity, density, and earthquake parameters, are used to construct the subsurface model. The results show that seismic wave propagation is strongly influenced by variations in subsurface properties. High amplification occurs in regions characterized by low shear-wave velocity and thick sediment layers. Quantitatively, amplification exceeds 2.0 in areas with shear-wave velocity below 2000 m/s, while regions with higher velocity (>3000 m/s) exhibit lower amplification values. The application of multi-parameter inversion improves the resolution of subsurface structures and enhances model accuracy. The spatial distribution of amplification identifies zones that are more susceptible to strong ground motion, confirming the dominant role of subsurface heterogeneity in controlling seismic response. This study provides a quantitative and dynamic framework for understanding seismic wave behavior and offers a robust basis for seismic hazard assessment and earthquake risk mitigation in the Java subduction zone